Routine Histopathological Evaluation of Benign Anorectal Interventions: Essentiality or Excess? - Ramazan Kozan; Enes Aksu; Kürşat Dikmen (Gazi Medical Journal)
Objective: To evaluate the necessity of routine histopathological examination in benign anorectal surgeries and to explore the potential for a selective approach based on patient characteristics. Methods: Retrospective analysis of patients who underwent surgery for benign anorectal diseases between January 2013 and December 2023. Demographic data, surgical procedures, and histopathological findings were assessed. Results: Among 830 patients, 482 underwent histopathological examination. No malignancy was detected. However, human papilloma virus (HPV)-related lesions were diagnosed in 2.1% of patients. A retrospective design and limited patient population were identified as major limitations. Conclusion: Routine histopathological examination may be unnecessary for benign anorectal surgeries in patients without HPV-related risk factors. Further large-scale studies are required to determine the criteria for selective examination, optimizing resource usage in clinical practice.